Research on fracture mechanism of rock mass with orthogonal cracks under uniaxial compression - Xuehua Li (PLoS ONE, 2026)
The initiation, expansion and penetration of cracks in rock masses are important reasons for rock mass failure. Orthogonal crack is the most typical form of cracks. There is still a lack of in-depth and detailed research on the law of expansion and penetration of orthogonal cracks. In this paper, the RFPA software is used to study the failure process of the rock mass with orthogonal fractures, and the influence of the change of the angle α between the main fracture and the loading direction on the failure mode and the failure mechanical properties of the specimen is comprehensively explored. The simulation results show that the angle α between the different main fractures and the loading direction affects the internal stress state of the rock, redistributes the stress field at the tip of the fracture and the surrounding area, resulting in the difference in the energy required for the expansion of the new fracture, which is manifested in the macroscopically as the difference in the strength of the rock and acoustic emission quantity.